Konsep Istinbath Hukum Kontemporer Menurut Said Ramadlan Al Buthi - Abdul Basith (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
The result development of era diverse contemporary problems we are facing automatically increase, many contemporary issues that need legal solutions, on the other hand the existing methodology is sometimes considered inadequate to provide tailored solutions for the benefit required. One of the determination law methods initiated by contemporary scholars is al-Bûthi’s concept of maslahat. His intellectual career that get many scholars’ attention, the high appreciation from the other scholars because of his personal charisma, and the uniqueness of his thoughts attract researchers to conduct the study on his concept of thought about maslahat. Based on this background the researcher interested to discuss about contemporary concept of istinbath according to Sa'id Ramadan al-Bûthi, then its application in the determination of Islamic law, also the relevance and significance for solving problems of the contemporary issues in Indonesia. The purpose of this study was to describe the contemporary concept according to Sa'id Ramadan al-Bûthi, then its application in the determination of Islamic law in Indonesia, also the relevance and significance for solving problems of the contemporary issues. The conclusion of this research is that contemporary concept of istinbath according to al-Bûthi must use istishlahi method, not the textualy one, only applying the text without being contextualized with the times and condition, nor too free without limitation when taking rests using the basis of maslahah, according to Sa'id Ramadan al-Bûthi the concept of istinbath law using maslahat considerations must fulfill five limits or restrictions (dlawâbith), namely: (1) maslahat must be ranged within the scope of the purpose of sari'ah '(maqâshid as-syari'ah), (2) does not contradict with al-Quran, (3) does not contradict with the Sunnah, (4) does not contradict with al-Qiyas, (5) does not ignore maslahat more important and urgrnt. Application of the Bûthi’s concept of maslahat for example is the determination of the law of jihad, the establishment of intellectual property rights, charity profession, waqf the money, etc.. From this it can be seen the relevance and significance of the the Bûthi’s concept of maslahat to be applied for solving contemporary problems in Indonesia.